Mobile Application Dictionary for Hearing Impaired Students (International Journal of Innovative Computing, 2019)
Mobile applications have been acknowledged by societies as a support tool that can be accessed everywhere via smartphone or any handheld device. The use of technology nowadays is not only limited to normal people; it can also be used by the disable community. Hearing-impaired people usually receive education via sign language and the dictionary is one tool used in schools to teach hearing-impaired students. There are several issues related to sign language dictionary such as the thickness of dictionary which makes it difficult to bring anywhere. Besides, teachers and students need to take longer time to access the targeted information. This research is conducted based on two main aspects: development of mobile application for the dictionary for the hearing-impaired and evaluation involving experts in the related research. This mobile application has been developed based on the Software Development Model of Mobile Application Dictionary. This model consists of five phases, which are analysis, design, development, prototyping and evaluation. The evaluation on mobile application for the dictionary involved four experts who have evaluated the interface design and learning design. The human computer interaction for mobile principles, dual coding theory, cognitive load theory, and multimedia theory have been used in the development of the dictionary. Based on the experts’ review, it is found that the value of content validity index is 0.91 for the features of interface design and 0.83 for learning design. Hence, this shows the value of content validity index is acceptable. The research aim is to improve the quality of sign language learning for hearing-impaired students and community related to them.
Keywords: Hearing impaired; mobile application; dictionary; human computer interaction; usability; heuristic